Avaliação experimental da rigidez de ligações pregadas e parafusadas em madeira - Freitas, Taís Oliveira Gonçalves (2017)
The connections are used to transfer all project loads between the elements, becoming relevant for timber structural design. The slip moduli connection has a direct influence in the mechanical behavior of timber structures as displacements and internal stress. There are several factors make an influence on slip moduli connection such as type, spacing, number of connection and the physical characteristics of used materials. The most used connection in Brazil between wooden elements are the metallic dowel, bolted and nailed connections. The current Brazilian timber structures standard ABNT 7190 (1997) does not present a design model for the slip moduli connection, however, there are international standarts tha present a design methodology for slip moduli connections. This paper present an methodology in order to evaluate the different models present through the CEN EUROCODE 5 (2004) standard, experimental analysis were realized in sample parts of Garapeira (Apuleia leiocarpa) and Caixeta (Tabebuia cassinoides), brazilian native wooden. The first one is characterized for medium-high density and the second as low-density. Two types of connectors were studied: bolts with nut and washers, and straight nails with head. The results show that the tests were satisfactory for nailed connections. For bolted connections, more studies of stiffness should be made.